2001
DOI: 10.1074/jbc.m101014200
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Induction of SOCS-2 and SOCS-3 mRNA Expression in C2C12 Skeletal Muscle Cells Is Mediated by Stat5*

Abstract: Previously, by a yeast 2-hybrid screen, we identified signal transducer and activator of transcription 5b (Stat5b) as a substrate of the insulin receptor (IR). We demonstrated that refeeding of fasted mice leads to rapid activation of Stat5 proteins in liver, skeletal muscle, and fat, suggesting that Stat5b is a physiological target of insulin. Here, we show that injection of glucose or insulin into fasted mice leads to robust activation of both Stat5a and Stat5b in skeletal muscle. In C2C12 myotubes, we find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 47 publications
3
44
1
2
Order By: Relevance
“…Treatment with human rG-CSF resulted in a dramatic increase of SOCS-3 mRNA within 45 min. This rapid induction of SOCS-3 was similar to that observed with other cytokines (47)(48)(49) and this indicates that SOCS-3 is an immediate early gene induced by G-CSF to rapidly modulate G-CSFR-mediated signaling. The strong and rapid induction of SOCS-3 mRNA in myeloid cells by G-CSF reported in this study, together with the previously reported potent induction of SOCS-3 by G-CSF, GM-CSF, and IL-3 in bone marrow cells (22), is a strong indication for SOCS-3 being an important regulator of signal transduction in immune cells.…”
Section: Discussionsupporting
confidence: 82%
“…Treatment with human rG-CSF resulted in a dramatic increase of SOCS-3 mRNA within 45 min. This rapid induction of SOCS-3 was similar to that observed with other cytokines (47)(48)(49) and this indicates that SOCS-3 is an immediate early gene induced by G-CSF to rapidly modulate G-CSFR-mediated signaling. The strong and rapid induction of SOCS-3 mRNA in myeloid cells by G-CSF reported in this study, together with the previously reported potent induction of SOCS-3 by G-CSF, GM-CSF, and IL-3 in bone marrow cells (22), is a strong indication for SOCS-3 being an important regulator of signal transduction in immune cells.…”
Section: Discussionsupporting
confidence: 82%
“…Recent studies have implicated a role for IRS-1 as a negative regulator of differentiation (Wang et al, 1993;Kim et al, 1998;Sadowski et al, 2001). Activated IRS-1 is a frequent event associated with different kind of human tumors (breast cancer, leiomyomas, Wilms' tumors, rhabdomyosarcomas, liposarcomas, and adrenal cortical carcinomas; Chang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Our novel findings are summarized as follows: (1) IRS-1 is expressed and activated in self-renewing ES cells; (2) IRS-1 protein expression levels are down-regulated upon LIF withdrawal and induction of ES cell differentiation; (3) LIF induces tyrosine phosphorylation of IRS-1 in self-renewing ES cells; (4) Reduction of IRS-1 expression by siRNA causes differentiation of ES cells even in the presence of LIF, down-regulating Oct4 protein expression and AP activity; (5) Targeting of IRS-1 impairs the capacity of LIF to induce PI3K dependent signals, resulting in a decrease of AKT and GSK-3b phosphorylation; (6) IRS-1 targeting results also in the down regulation of both Id1 and Id2 proteins expression; (7) Although there is a substantial literature on the role of IRS-1 in cell proliferation and differentiation (Wang et al, 1993;Kim et al, 1998;Shima et al, 1998;Bohni et al, 1999;Valentinis et al, 2000;Brogiolo et al, 2001;Sadowski et al, 2001), information on its functions in ES cells is lacking. In the current study we show that the presence and activation of IRS-1 is critical for LIF mediated self-renewal of ES cells.…”
Section: Discussionmentioning
confidence: 99%
“…Both insulin and Ang II are individually able to induce the expression of SOCS proteins in tissues of living animals and in cultivated cell-lines [68][69][70][71][72]. Depending on the tissue or cell line studied, insulin is able to induce the expression of SOCS-2 [69] and/or SOCS-3 [68,73] through the activation of STAT-5b.…”
Section: The Late Events Affected By the Insulin-ang II Cross-talkmentioning
confidence: 99%
“…Depending on the tissue or cell line studied, insulin is able to induce the expression of SOCS-2 [69] and/or SOCS-3 [68,73] through the activation of STAT-5b. Once induced, SOCS-3 can bind to the Tyr 960 of the IR and hamper its capacity to induce the tyrosine phosphorylation of STAT5b, IRS-1 and IRS-2 [68,70,74].…”
Section: The Late Events Affected By the Insulin-ang II Cross-talkmentioning
confidence: 99%